2022
DOI: 10.1249/mss.0000000000003072
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Motor Planning and Response Selection after Anterior Cruciate Ligament Reconstruction

Abstract: Purpose: The purpose of this study is to compare cortical motor planning activity during response selection and motor execution processes between individuals with anterior cruciate ligament reconstruction (ACLR) and uninjured controls during a reaction time and response selection task. Methods: Individuals with ACLR (n = 20) and controls (n = 20) performed a lateralized choice reaction time (e.g., Go/NoGo) task. Electrocortical activity and reaction time were recorded concurrently using electroencephalography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Two prospective studies have identified decreased brain functional connectivity between cortical sensory and motor regions before ACL injuries (10,11). This altered connectivity may lead to an inability to react to environmental changes such as opponent behavior during dual tasks (15,19). Interestingly, alterations in brain regions responsible for proprioceptive reweighting have been reported after ACL injuries (20)(21)(22) and could further explain the risk of recurrences.…”
mentioning
confidence: 99%
“…Two prospective studies have identified decreased brain functional connectivity between cortical sensory and motor regions before ACL injuries (10,11). This altered connectivity may lead to an inability to react to environmental changes such as opponent behavior during dual tasks (15,19). Interestingly, alterations in brain regions responsible for proprioceptive reweighting have been reported after ACL injuries (20)(21)(22) and could further explain the risk of recurrences.…”
mentioning
confidence: 99%